Representative Acts in Dalia Mogahed's Speech "What it's Like to Be a Muslim in America" (NOBEL: Journal of Literature and Language Teaching, 2022)
This present study aims to investigate various kinds of representative acts performed in Dalia Mogahed's speech entitled "What It's like to be a Muslim in America?" and to analyze the Islamic values that may be contained in the speech. As a qualitative research, the data of the current study were collected by searching and watching speech videos on Youtube and downloading the videos and the speech transcripts. In investigating the representative acts of Dalia Mogahed, this study applied Searle's (1976) theory of representative speech acts in analyzing the data in the forms of utterances produced by Dalia that were collected from Dalia's speeches.  The data that have been obtained were then classified, analyzed, interpreted, and described. The results show that Dalia's 111 utterances were identified as representative acts, consisting of 54 utterances of stating, 32 utterances of describing, 10 utterances of asserting, 9 utterances of informing, 3 utterances of reporting and 3 utterances of predicting. The representative acts in Dalia's speech are reported to contain some Islamic messages.